Efficient fully roll-to-roll coated encapsulated organic solar module for indoor applications. (15th May 2021) - Miranda, Bárbara H.S.; Corrêa, Luiza de Q.; Soares, Gabriela A.; Martins, Juliana L.; Lopes, Paulo L.; Vilela, Maria L.; Rodrigues, Jair F.; Cunha, Thainá G.; Vilaça, Rodrigo de Q.; Castro-Hermosa, Sergio; Wouk, Luana; Bagnis, Diego
Highlights: Flexible solution-processed Organic Photovoltaics successfully produced and scaled-up. Thicker active layer films leading to high indoor performances. Fundamental role of layer's uniformity for high-indoor performances. Importance of low light intensities study when evaluating devices for indoor applications. The need of an in-depth study of Organic Photovoltaics structure dedicated to low light conditions. Abstract: The recent development of 5G networks has enabled the internet of things (IoT) to emerge as a key factor in the growing global data network. For the IoT, not only are sensors required, but also alternative ways to supply them with the energy they need. Organic photovoltaics (OPV) are a promising solution for energy harvesting and self-generation for low-consumption sensors since they have excellent physical, optical and electrical properties, including being lightweight, having shape freedom, broad-range absorption spectra, semi-transparency, and they are highly efficient even in extremely low-light environments. Here, we report, encapsulated OPV module optimized for indoor applications delivering 18% power conversion efficiency (PCE) under 400 lx LED illumination. All modules were fabricated and encapsulated in air using totally scalable roll-to-roll (R2R) slot-die coating and screen-printing methods made on flexible substrates with non-toxic solvents.